HAK WARIS ANAK PEREMPUAN TIONGHUA DALAM PRESFEKTIF HUKUM (STUDI DI KABUPATEN SEKADAU) - Michell eko Hardian (Universitas Kapuas Sintang, 2021)
The Tionghoa community is one ofLegislation of Civil Law (Burgelijk Wetboek), it is displaying the existence of legal pluralism in Indonesia.the societies that populated for a long time and it is almost evenly spread in Indonesia. In several case of Tionghoa communities especially in terms of inheritance, a Tionghoa customs is continued to be used which are intended to regulate the differences rghts of boys and girls. In Tionghoa culture, boys are at high position because they are the successors of the clan (clan), contrariwise in Legislation of Civil Law (KUH Perdata) the position of girls and boys are equal. The gap of this differences fascinates the author to apply a research that will be published as a journal with the identification of the problem: How is the inheritance rights of Tionghoa girls toward the inheritance distribution in a legal perspective.This research uses a sociological juridical approach as means of a qualitative method. It is intended to provide a detailed explanation of the phenomenon which difficult to convey in form of quantitative method, to describe the differences between inheritance law that applies to Tionghoa communities and the inheritance legal system according to theThe results of this research confirm an essential difference between the customs and habits of Tionghoa communities and the inheritance legal system according to the Legislation of Civil Law (Burgelijk Wetboek), namely the Tionghoa Indonesian community assign the son as a truly successors of the inheritance of their parents. Therefore, the position of sons is more higher than girls because of the inheritance of the clan. In other hand, the girl does not obtain rights to inherit because the girl will follow her husbands when married.In Legislation of Civil Law (The position of girls and boys are equals, because the Legislation of Civil Law especially adheres to an individual inheritance system, bilateral and parental. In addition to these, the Legislation of Civil Law also know the terms of absolute part of the inheritance (legitime portie), whereas according to customary law; the position of Chinese is different, where the position of boys is higher than girls, this is because boys will take a responsibility to carry the name of their clan (clan) endlessly to the next descendants.The author recommend suggestions consider with with today’s developments and to accomplish the demands of a sense of justice, it is better for girls inherit without being discriminated. Meanwhile, the customs and culture are entrenched. However, a compromise is the middle way as resolution. It is consider with the inheritance law of Indonesia occurs a legal pluralism that influenced by religion, ethnicity and customs, therefore customary laws that was born from the traditions of the Tionghoa community enable to be enforced.